Evaluasi Aksesibilitas Pengguna Pada Platform Merdeka Mengajar Dengan Web Content Accessibility Guideline 2.2 - Nurhady, Rizki Ramadiansyah; Hadi Putra, Panca (The Indonesian Journal of Computer Science, 2025)
Web accessibility evaluation of government platforms is crucial for inclusivity. This study assesses the accessibility of Platform Merdeka Mengajar (PMM), a digital platform developed by Indonesia's Ministry of Education for teachers and educational staff. The focus is on evaluating PMM's compliance with web accessibility standards, considering the importance of inclusivity in digital education, especially for visually impaired users. Methodology involves evaluation based on Web Content Accessibility Guidelines (WCAG). Results reveal 450 accessibility issues across 94 PMM pages, including problems with non-text content, information relationships, color contrast, link purpose, headings, labels, and element naming. Recommendations for fixing accessibility issues are provided for 43 pages meeting A and AA conformance levels. In conclusion, PMM requires significant improvements to become more inclusive, and this research presents recommendations based on WCAG standards to enhance the platform's accessibility.